Internal Delegation Contracts for Water in Uganda : An Innovative Approach to Establishing a Successful Public Utility - Marin, Philippe; Muhairwe, William; Mugisha, Silver; Mugabi, Josses (World Bank, Washington, DC, 2012)
Uganda's national water utility has become known for its successful turnaround under public management. Less well known is that this success owes much to the introduction of private-sector-like practices to motivate employees. Following a mixed experience with two short-term management contracts in Kampala, the utility's management introduced an innovative concept of internal delegation, inspired by public-private partnership contracts. Local managers establish private partnerships to operate systems under contract with the utility, with part of their pay depending on performance. The experience offers interesting lessons for those involved in reforming urban water utilities in developing countries.